2014
DOI: 10.1007/s00467-014-2964-7
|View full text |Cite
|
Sign up to set email alerts
|

44-h ambulatory blood pressure monitoring: revealing the true burden of hypertension in pediatric hemodialysis patients

Abstract: The 44-h ABPM provides more information than the 24-h ABPM in terms of diagnosing and assessing the true burden of hypertension in pediatric HD patients. Elevated BP loads from 44-h ABPM correlate with a higher LVMI on the echocardiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Paglialonga et al retrospectively analyzed 16 oligoanuric children and found significant correlation between IDWG and left ventricular mass index (LVMI) with significant correlation between IDWG and DBP [3]. Haskin et al performed 44 hr ambulatory blood pressure monitoring (ABPM) on 13 pediatric HD patients and found that with longer monitoring (1 day versus 2 days) more pts were found to be hypertensive, with moderate positive correlation between BP and IDWG, concluding that as fluid accumulates during the interdialytic period it contributes to increased BP load [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paglialonga et al retrospectively analyzed 16 oligoanuric children and found significant correlation between IDWG and left ventricular mass index (LVMI) with significant correlation between IDWG and DBP [3]. Haskin et al performed 44 hr ambulatory blood pressure monitoring (ABPM) on 13 pediatric HD patients and found that with longer monitoring (1 day versus 2 days) more pts were found to be hypertensive, with moderate positive correlation between BP and IDWG, concluding that as fluid accumulates during the interdialytic period it contributes to increased BP load [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other studies in pediatric hemodialysis, our study has disadvantages that include small number of subjects, retrospective design, and single center experience [2, 3, 11]. As only retrospective data that were part of routine clinical care were collected, our study lacks dietary salt intake records, ambulatory blood pressure monitor studies, 3 or more BP measurements before HD, daily urine output, daily weight, and ambulatory BP measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Role of IDWG in HTN is unclear. While some report overhydration as the main cause of HTN, others find that it is frequently not associated with HTN, in both adults and children . Recommendations to decrease dNa are made to improve IDWG by decreasing Na load and thirst .…”
Section: Discussionmentioning
confidence: 99%
“…While some report overhydration as the main cause of HTN, others find that it is frequently not associated with HTN, in both adults and children. 2,8,9,27,[38][39][40][41] Recommendations to decrease dNa are made to improve IDWG by decreasing Na load and thirst. 2,7,42 Aggressive fluid removal used for high IDWG may lead to intradialytic hypotension, with reduction of blood flow to vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitors reduce left ventricular mass and decrease the mean arterial blood pressure. 32,33 In hypertensive pediatric dialyzed population, renal artery stenosis is not frequent, and other contraindications, such as pregnancy and breast-feeding, can be neglected. Thus, this group of drugs both with ARB seems to be the safest.…”
Section: New Scopes For Better Blood Pressure Controlmentioning
confidence: 99%